Engineering of electrical contacts on 2D-semiconductor field-effect transistors - Ullman, Patrik (My University, 2024)
Two-dimensional (2D) semiconductor materials, such as the transition metal dichalcogenides (TMDC), have attracted great attention in the last decade due to their excellent electronic properties, thin nature, free of surface dangling bonds, and ability to retain high carrier mobility down to atomic thickness. TMDCs such as Molybdenum disulfide (MoS2) have the potential to be integrated into and augment conventional silicon complementary metal-oxide semiconductor (Si-CMOS) technology for post-Moore’s law technology. However, the performance of 2D field-effect transistors (FETs) are largely limited by poor charge carrier injection at the metalsemiconductor (M-S) interface, owing to a large Schottky barrier due to metalinduced gap states (MIGS) and fermi-level pinning (FLP). In this work, exfoliated MoS2-FETs were fabricated and various contact engineering approaches were proposed to mitigate MIGS, to achieve efficient carrier injection. The M-S junction of gadolinium and bismuth has been investigated using state-of-the-art fabrication methods and electrical measurement techniques. Semi-metal Bi has the ability to suppress MIGS due to its near-zero density of states (DOS) near the chargeneutrality point (CNP), while gadolinium is in theory able to lower the Schottky barrier by work function tuning. Key parameters were extracted by performing temperature-dependent I-V measurements, as well as height profile analysis by AFM. It was found that both bismuth and gadolinium have the potential to be considered as good ohmic contacts to MoS2, owing to their low SBH of ϕ ≈ 43 meV and ϕ ≈ 56 meV, respectively. This thesis work sheds light on the challenges of contact en gineering and fabrication methods for 2D-FETs.
Keywords: FET, contacts, 2DMs, TMDC, MIGS, MoS2, FLP, SBH